Ungkapan Penerimaan dan Penolakan dalam Transaksi Jual Beli di Pasar Panciro Kabupaten Gowa - Wahyu MS; Andi Agussalim AJ; Hajrah Hajrah (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract.This study aims to describe the form of the expression of acceptance and rejetion in buying and selling transactions in the Panciro market, Gowa Regency. Type and the design of this research is descriptive qualitative. Data in this study is an expression or conversation between a seller and a buyer in the form of sentences at the time of buying and selling transactions at the Panciro market, Gowa Regency. Technique used are data collection techniques, data reduction, data presentation, and drawing conclusions. The object of this research is the expression between the seller and buyers when making buying and selling transactions at the Panciro market, Gowa Regency. The result of this study found that there were five forms of acceptance expressions, namely: interested pragmatic effect, happy pragmatic effect, sympathetic pragmatic effect, effect pragmatics persuades, pragmatic effect convinces. and there are five forms expressions of rejection, namely rejection with direct words, rejection with reasons, refusal by using conditions, refusal by interjection, and refusal with an apology. Then analyzed based on pragmatic theory.Keywords: Expression, acceptance, rejection, seller, buyer, transaction